Value of follow-up CT in head injury assessment - Owen, Jeannine Margaret (Division of Radiology, 2015)
INTRODUCTION: The question of when and if to perform follow- up CT scanning of the brain in a patient with a proven head injury remains pertinent, and the answer is not clear cut. This is even more so compounded when one tries to compare and equate what happens in a developed country with that of a developing country such as South Africa. AIM: To evaluate referral patterns, associated time-delays and findings of follow-up CT as well as patient outcomes in patients with head injury at Groote Schuur Hospital. METHOD: A retrospective review, over a 6 month time period, of the CT scans and folders belonging to patients who underwent follow-up CT scanning of the brain after blunt trauma to the head. RESULTS: There were 313 follow-up studies performed in 212 patients, of which the majority, 135 /313 (43.1%) were referred for neurological reasons, whilst 103/313 (32.9%) were referred for conservative management reasons and 75/313 (24%) were referred as part of their post-surgical check-up. There were significant time delays from arrival of patients in casualty to their initial CT scan (mean 18.74 hours) as well as between the initial CT and the first follow-up scan (mean 121.78 hours). There was a significant amount of data missing regarding the time of actual injury for many patients. There were 74 neurosurgical interventions that took place as a result of CT scans performed. Of these, 54 (73%) took place after the initial CT scan, whilst only 20 (27%) occurred after a follow-up CT. Of those surgical interventions performed after a follow- up study, 6 (30%) were performed as a result of a scan performed for post-surgical check- up. 12 (60%) were performed as a result of a scan performed for neurological reasons. Two (10%) neurosurgical interventions occurred as a result of a scan performed for conservative management reasons (thus routine follow-up imaging). CONCLUSIONS: A routine single follow-up CT may be a reasonable approach with further follow-up imaging reserved for patients who have undergone surgery, those with possibly surgically manageable findings on initial CT (that do not undergo surgery) and those with new neurology. The routine use of follow-up CT beyond the first follow-up CT is unlikely to lead to a change in management when the above clinical, and prior CT findings are absent. However, the time delays across all aspects of imaging traumatic brain injuries in our setting are unpredictable and represent a major problem in standardising when CT scans are performed.